The economic impacts of transportation towards the in-field post-handling practices of oil palm plantation / Muhamad Safuan Baharudin - Baharudin, Muhamad Safuan (Faculty of Plantation and Agrotechnology, 2016)
Oil palm plantation need to be managed efficiently to maintain the performance of oil palm to produce yield each year. One of the important things that need to be care about is transportation. Transportation in oil palm plantation has been divided into two which are transportation to the mill and in-field transportation that both involve in post-handling in oil palm plantation management. Transportation that involve in in-field handling must be studied to know the efficiency and yield input that can be derived to the economic impact. In this study, conventional and mechanization system was compare. Wheel barrow representing conventional system and mini tractor representing mechanization in transportation system. The cost, yield and area coverage data for the year 2015 was collected from the FELCRA Berhala Gantang, Temerloh, Pahang. The data used to know which transportation is worth to be implemented. The study shows mini tractor is the better transportation that can be used in in-field handling compared to conventional system.